The Lady of Guadalupe - De Paola, Tomie (New York Holiday House, 1980)
Recounts the appearance of the Lady of Guadalupe to a poor Indian farmer in Mexico in 1531.
Keywords: Juan Diego -- Saint -- 1474-1548.; Guadalupe, Our Lady of